THE EFFECT OF CAPITAL STRUCTURE, RUPIAH EXCHANGE RATE AND COMPANY GROWTH ON THE INDONESIA STOCK EXCHANGE - Ayunda, Khalifa Damalin; Rufiatun, Yayuk; Najla, Aura Nabilat En Najla (Jurnal Manajemen dan Bisnis, 2026)
This research aims to examine the influence of capital structure, rupiah exchange rate and company growth on company value with profitability as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (BEI). This type of research is quantitative research with an associative approach. Sampling in this study used purposive sampling with a total sample of 27 food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2018-2022. The data analysis method in this research uses Panel Data Regression analysis. The results of this research show that capital structure has no effect on company value, the rupiah exchange rate has a significant effect on company value, company growth has no effect on company value, Profitability moderates capital structure on company value, the rupiah exchange rate moderates the rupiah exchange rate on company value and Profitability does not moderate growth company on company value and simultaneously capital structure, rupiah exchange rate and company growth influence company value